Diversity, function, and transcriptional regulation of gut innate lymphocytes - Rankin, Lucille; Groom, Joanna; Mielke, Lisa; Seillet, Cyril; Belz, Gabrielle (Frontiers in Immunology, 2013)
The innate immune system plays a critical early role in host defense against viruses, bacteria and tumour cells. Until recently, natural killer (NK) cells and lymphoid tissue inducer (LTi) cells were the primary members of the innate lymphocyte family: NK cells form the front-line interface between the external environment and the adaptive immune system, while LTi cells are essential for secondary lymphoid tissue formation. More recently, it has become apparent that the composition of this family is much more diverse than previously appreciated and newly recognized populations play distinct and essential functions in tissue protection. Despite the importance of these cells, the developmental relationships between different innate lymphocyte populations (ILCs) remain unclear. Here we review recent advances in our understanding of the development of different innate immune cell subsets, the transcriptional programs that might be involved in driving fate decisions during development, and their relationship to NK cells.